Caracterização morfométrica e molecular de populações de bicudo do algodoeiro - Santos, Sabrina Kelly dos (2020)
In Brazilian territory, cotton is one of the main agricultural crops, however, it has as an obstacle the presence of the weevil, Anthonomus grandis Boheman (Coleoptera: Curculionidae), the main pest of this crop, which when attacking flower buds and apples, causes a decrease in production. Morphometric studies together with the use of molecular markers can help to understand genetic diversity within and between different populations of plant and animal species and consequently implement more effective integrated pest management. The present work aimed to evaluate morphometrically and by means of molecular markers the dissimilarity among ten populations of boll weevil. The weevil populations came from different locations in Brazil. Morphometric measurements and molecular tests were performed at the Entomology and Biotechnology Laboratories, respectively, both located at Embrapa Cotton, in the city of Campina Grande, PB. Fifty weevils were separated from each population, photographed with a 13 mega pixel camera coupled to a stereoscopic microscopic, the images were transferred to a computer and measurements of the physical structures of the insects were performed using the Image J. Software. For molecular characterization, genomic DNA from fifteen weevil from each population was used, previously analyzed for morphometry. DNA was extracted by the CTAB method and PCR reactions were conducted using ISSR primers from the University of British Columbia. For analysis of morphometric data, the means were compared using the Scott-Knott test (P≤0.05). For molecular data, the measures of dissimilarity were obtained by the Nei coefficient and the grouping done by the hierarchical method UPGMA and Tocher of optimization. In addition, the correlation between genetic distance and geographical distance in kilometers (straight line) was evaluated. All data were analyzed using the GENES Software. The population of Chapadão do Sul presented higher averages than the other populations in nine characteristics, whereas the population of Campina Grande presented the lowest in eleven evaluated characteristics. The highest rate of polymorphism was observed in the populations of Ipiranga do Norte and Campina Grande, with a percentage of 82% and 77%, respectively, and the lowest rate of polymorphism was found in the population of Primavera do Leste (30%). By Tocher of optimization method, three groups were formed and in the UPGMA cluster analysis, five groups were formed when the 70% cutoff point was adopted, which corresponds to the 0.320 genetic distance. Based on the morphometric characteristics and the evaluation with ISSR markers, it is possible to infer that there is genetic variability between and within the populations of weevil from different locations in Brazil. The results obtained in this work provide information on different populations of cotton weevils, thus contributing to the development and/or improvement of a more efficient management of this pest.